Pragmatic failure in the realization of the speech act of responding to compliments among Yemeni EFL undergraduates - Al-Ghamdi, Namiah Ahmad; Almansoob, Najeeb Taher; Alrefaee, Yasser (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of the present study is to investigate into the possibility of pragmatic failure in the L2 production of Yemeni EFL university learners. It, in particular, tackles the L1 negative pragmatic transfer in the speech act of responding to compliments. The participants of the study are thirty Yemeni learners of English representing the target group and two baseline groups: thirty Yemeni Arabic native speakers and thirty American English native speakers. The researchers used a Discourse Completion Task as to collect the relevant data based on six complimenting scenarios. Data were codified into compliment response formulas and analysed statistically via SPSS in terms of the overall frequency counts of the semantic formulas. The results revealed that pragmatic failure is highly evident in the learners’ L2 production. L1 negative pragmatic transfer occurred in the response strategies of 'Comment Acceptance', 'Comment History', 'Praise Upgrade', 'Return', 'No Acknowledgement', 'Offer', 'Promise' and 'Wish'. They nearly represent 50% of the leaners' response utterances. The learners also showed a tendency of positively assimilating their L2 norms in the realization of compliment responses in half of their response utterances.